Integration of GRC and ESG in Hospital Risk Management and Its Impact On Sustainability - Robertus Maria Bambang Gunawan (Eduvest - Journal of Universal Studies, 2024)
Hospitals face complex and evolving risks as regulations, patient expectations and operational challenges change. Integration of Governance, Risk, and Compliance (GRC) and Environmental, Social, and Governance (ESG) is important to ensure holistic risk management and hospital sustainability. This study aims to analyze the concept of GRC and ESG integration in hospital risk management. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that GRC and ESG in hospital risk management have a significant impact on operational sustainability. GRC ensures that hospitals have a strong framework for managing governance, risk and compliance, which is important for maintaining operational stability and avoiding legal issues. ESG, on the other hand, emphasizes the importance of environmental, social and governance responsibilities in the day-to-day operations of hospitals. So by integrating GRC and ESG, hospitals can identify and manage risks more comprehensively, from compliance with health regulations to the environmental and social impacts of operations.